Optimizing Digital Transformation Through AI and Cloud Technology Integration for Innovation in Big Data-Driven Information Systems - Giantri, Lilik Tiara; Hudzaifah, Muhammad; Suciana, Ewin; Arief Christanto, Duta; Cahyadi, Dede (Politeknik Negeri Batam, 2025)
Digital transformation has become critical for SMEs in emerging economies, yet integrated studies combining AI, cloud computing, and human factors remain scarce. This study addresses this gap by developing a holistic framework for Indonesian SMEs through a systematic literature review. Using PRISMA protocol, we analyzed 46 peer-reviewed articles (2020-2025) from Scopus, IEEE Xplore, and Google Scholar, with thematic synthesis in NVivo 12. The proposed framework reveals three interdependent dimensions: (1) technological integration (AI-cloud-big data synergy), (2) process optimization (automation and analytics), and (3) human-digital leadership (competency and cultural readiness). Case studies show 35% operational efficiency gains but highlight infrastructure and skill gaps. This study contributes a novel integration of TOGAF and DCMM theories, offering policymakers a roadmap for SME digitalization while cautioning against one-size-fits-all solutions.